If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15(3-6x)=24x=45
We move all terms to the left:
15(3-6x)-(24x)=0
We add all the numbers together, and all the variables
15(-6x+3)-24x=0
We add all the numbers together, and all the variables
-24x+15(-6x+3)=0
We multiply parentheses
-24x-90x+45=0
We add all the numbers together, and all the variables
-114x+45=0
We move all terms containing x to the left, all other terms to the right
-114x=-45
x=-45/-114
x=15/38
| 9m-5=5m+27 | | 7/8/x=2/3/4/7 | | 1x+6=4x+9 | | –3t−6=–4t | | 12+8x=47 | | 6k-9=3k+9 | | 4x-32=3x+6 | | -7/3u=21 | | 2x-1.5=31.8 | | 6a-a-4a=8 | | 13=k4 | | 9t+7=3t+19 | | -78=-6f | | -4(4u-2)+8u=4(u+6) | | 4j+4=3j+11 | | 3.6n+2.3n=25.3+10.1 | | 8u-8u+u=6 | | -12=v+7 | | 6(4b+4)=0 | | (9x-1)=(8.5x+2) | | 6x+3−3x=0 | | 3n.n=11 | | 15=3+4d | | x=3+1/4 | | -15/2=60/x | | m+487 =9m= | | −34a=−9 | | -2(b+5)-3=11 | | 6(x/2-3)+10=-32 | | 8i-6=5i+6 | | 9y+3•(-3y+6)=18 | | 16z-6z-z=9 |